2022
DOI: 10.54986/irjee/2022/oct_dec/106-111
|View full text |Cite
|
Sign up to set email alerts
|

Procedural Impediments in e-NAM System Faced by Stakeholders in Guntur Mandi of Andhra Pradesh

Abstract: The study was conducted on the e-NAM (online marketing platform) to study the perceived impediments faced by stakeholders of e-NAM of Guntur mandi in Andhra Pradesh in 2019-20. Data were collected from 100 respondents, of which 30 were farmers, 30 traders, 5 FPOs, 25 commission agents, and 10 e-NAM offi cials from the market using a specially designed interview schedule. Later constraints were prioritized through Garrett’s ranking technique. The fi ndings highlighted that the lack of awareness, depending on th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 4 publications
(4 reference statements)
2
3
0
Order By: Relevance
“…Noopur et al (2023) [12] pointed out that small and marginal farmers face challenges due to high transportation costs and a lack of storage facilities, hampering their ability to market produce effectively. The findings are in accordance with the studies reported by Bandhavya et al (2022) [10] , Kaur et al (2021) [13] , Bisen and Kumar (2018) [14] , Nirmal (2017) [15] , Gohain and Singh (2018) [16] , Kala et al (2020) [17] and Sonawane et al (2020) [18] .…”
Section: Constraints Faced By the Respondentssupporting
confidence: 91%
See 1 more Smart Citation
“…Noopur et al (2023) [12] pointed out that small and marginal farmers face challenges due to high transportation costs and a lack of storage facilities, hampering their ability to market produce effectively. The findings are in accordance with the studies reported by Bandhavya et al (2022) [10] , Kaur et al (2021) [13] , Bisen and Kumar (2018) [14] , Nirmal (2017) [15] , Gohain and Singh (2018) [16] , Kala et al (2020) [17] and Sonawane et al (2020) [18] .…”
Section: Constraints Faced By the Respondentssupporting
confidence: 91%
“…Lack of digital literacy was the problem as most of the farmers were from rural backgrounds with less education; they had difficulty accessing smartphones, mobile apps and other online features like modal price, arrivals, pre-registration, previous day transactions trend, market information, etc. Bandhavya et al (2022) [10] found that farmers had limited awareness of e-NAM due to their absence from the market. Many farmers sent their produce through commission agents, who primarily handled the e-NAM procedure, leaving the farmers less informed about the process.…”
Section: Constraints Faced By the Respondentsmentioning
confidence: 99%
“…Lal et al 12 used exploratory factor analysis (EFA) and identified 4 types of broad impediments viz., environmental constraints, pecuniary constraints, policy constraints and miscellaneous impediments and ranked by using Garrett ranking technique. Similar in-depth study had been carried out by Sinha et al, 13 Popoola et al, 14 Bandhavya et al, 8 Lal et al 15 Reviewing the above studies, this paper uncovers various impediments perceived by farmers in the cyclone affected region of Odisha.…”
Section: Introductionsupporting
confidence: 67%
“…It is also termed as hindrance or obstruction that limits a system from reaching its goal. 8 Different methodologies were used by researchers to rank the most critical constraints. Goyal et al 9 explored five broad constraints, viz., Social constraints, Communicational Constraints, Managerial constraints, Technical Constraints and Infrastructural Constraints perceived by veterinary surgeons in Haryana ranked by using Garrett ranking method.…”
Section: Introductionmentioning
confidence: 99%
“…To study behaviour based on gender is a key for all round development as of today due to industrialization, women involve in almost all the activities of any field from household chores to making policy of a country [6]. The role of farm women in both selling and purchasing of products on online portals is witness everywhere [7,8] and besides being a homemaker, the role and decision of women is paramount in every field [9] and as a customer as well in the dimension of consumer behaviour.…”
Section: Introductionmentioning
confidence: 99%